2011
DOI: 10.2478/s11535-011-0093-x
|View full text |Cite
|
Sign up to set email alerts
|

Phage therapy for plant disease control with a focus on fire blight

Abstract: The concept of using bacteriophages (bacterial viruses) as biocontrol agents in pest management emerged shortly after their discovery. Although research on phage-based biopesticides temporarily stopped with the advent of antibiotics, the appearance of antibiotic resistant bacterial strains led to a renewed interest in phage therapy for control of plant diseases. In the past twenty years numerous successful experiments have been reported on bacteriophage-based biocontrol measures, and several comprehensive stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
27
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 66 publications
0
27
0
Order By: Relevance
“…Bacteriophages (phages) offer a novel biological control mechanism since they are ubiquitous in the orchard environment, self‐replicating, nontoxic to eukaryotes, biodegradable unlike many agrochemicals and usually species and strain specific with no effect on indigenous bacteria. Phage‐mediated control of fire blight has been studied in laboratory and under field conditions (Erskine, ; Gill et al ., ; Lehman, ; Müller et al ., ; Svircev et al ., 2010; 2011; Boulé et al ., ; Schwarczinger et al ., ; Nagy et al ., ). Erskine () first demonstrated that a temperate phage that lysogenized a yellow saprophytic bacterium reduced fire blight symptoms when co‐inoculated with E. amylovora on pear slices.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bacteriophages (phages) offer a novel biological control mechanism since they are ubiquitous in the orchard environment, self‐replicating, nontoxic to eukaryotes, biodegradable unlike many agrochemicals and usually species and strain specific with no effect on indigenous bacteria. Phage‐mediated control of fire blight has been studied in laboratory and under field conditions (Erskine, ; Gill et al ., ; Lehman, ; Müller et al ., ; Svircev et al ., 2010; 2011; Boulé et al ., ; Schwarczinger et al ., ; Nagy et al ., ). Erskine () first demonstrated that a temperate phage that lysogenized a yellow saprophytic bacterium reduced fire blight symptoms when co‐inoculated with E. amylovora on pear slices.…”
Section: Introductionmentioning
confidence: 99%
“…carotovora (Faltus and Kishko, 1980;Ruban et al, 1981;Toth et al, 1993;Tovkach, 2002a,b) and P. agglomerans (previously known as Erwinia herbicola) (Harrison and Gibbins, 1975). Furthermore, the genomes of all fully sequenced E. amylovora phages lack the necessary genes for prophage integration (Lehman et al, 2009;Born et al, 2011;Nagy et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Bacteriophages specific for Er. amylovora were first reported several decades ago (Erskine, 1973), and more recently followed by studies regarding their characterization and application to control the pathogen (Schnabel and Jones, 2001;Gill et al, 2003;Born et al, 2011;Boulé et al, 2011;Müller et al, 2011b;Schwarczinger et al, 2011;Nagy et al, 2012). Clearly, the extreme specificity of phages to kill only their host bacteria without affecting other members of the bacterial ecosystem offers significant potential for environmentally friendly pathogen control.…”
Section: Introductionmentioning
confidence: 99%
“…These advances collectively paint phages not only as the most numerous and diverse biological entities on our planet, but also as regulators of microbial ecosystems through rapid infection cycles and gene transfer events (3-7). Yet, compared to their bacterial hosts, and despite their proven potential to transform fields such as medicine (8-10), agriculture (11, 12), and biotechnology (13-15), phages are, in general, poorly characterized (16-20).…”
Section: Introductionmentioning
confidence: 99%